PENERIMAAN NILAI – NILAI SOFT POWER MELALUI SERIAL DRAMA INDIA OLEH KHALAYAK INDONESIA - RESEN, PUTU TITAH KAWITRI; PRADIPTA, ADE DEVIA (Jurnal Ilmiah Widya Sosiopolitika; Vol 2 No 1 (2020): ISU PARIWISATA DAN KESEHATAN DALAM PERSPEKTIF SOSIAL DAN POLITIKDO - 10.24843/JIWSP.2020.v02.i01.p01, 2020)
This article aims at describing the use of drama series as an instruments of soft power, particularly Indian drama series which were aired in Indonesian national television channels. The specific objective of this study is to examine the opinion of Indonesian audiences toward the attractiveness power of the drama series as an instrument of soft power. This research is a descriptive qualitative research using literature study and in depth – interview method. Informants in this study were determined through purposive technique and snowball sampling. Using the concept of soft power, this study found that eventhough Indian drama series are considered quite attractive by Indonesian audiences, not all Indian drama series are able to build a positive image of India. Only th e drama series which contains high culture values ??can build positive image of the country . Keyword : India, Indonesia, audiences, drama series, soft power